2023
DOI: 10.3390/ijerph20042994
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia: Recent Advances in Predicting, Preventing, and Managing the Maternal and Fetal Life-Threatening Condition

Abstract: Preeclampsia accounts for one of the most common documented gestational complications, with a prevalence of approximately 2 to 15% of all pregnancies. Defined as gestational hypertension after 20 weeks of pregnancy and coexisting proteinuria or generalized edema, and certain forms of organ damage, it is life-threatening for both the mother and the fetus, in terms of increasing the rate of mortality and morbidity. Preeclamptic pregnancies are strongly associated with significantly higher medical costs. The mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 102 publications
1
14
0
3
Order By: Relevance
“…Although PE is a severe complication of pregnancy, its exact mechanism is not yet fully understood. 9 Some studies [10][11][12] Prior studies [22][23][24] have also shown that calculating modulus values, VI, FI, VFI indices, and perfusion scores may not be fully objective. When placental tissue is heterogeneous or non-directional, measurement errors can occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PE is a severe complication of pregnancy, its exact mechanism is not yet fully understood. 9 Some studies [10][11][12] Prior studies [22][23][24] have also shown that calculating modulus values, VI, FI, VFI indices, and perfusion scores may not be fully objective. When placental tissue is heterogeneous or non-directional, measurement errors can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Although PE is a severe complication of pregnancy, its exact mechanism is not yet fully understood 9 . Some studies 10–12 have hypothesized that, in normal pregnancy, placental formation occurs via the invasion of trophoblast cells into maternal spiral arteries, establishing low resistance and high flow maternal‐uterine‐placental circulation. In PE, the invasion of trophoblast cells into maternal spiral arteries is impaired, thus creating a hypoxic environment that can lead to abnormal differentiation of trophoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early in pregnancy, the nearly 50% increase in maternal cardiac output is ascribed primarily to increased stroke volume, whereas later increases are primarily due to elevated heart rate [10]. Although reduced systemic vascular resistance results in decreased systolic, diastolic, and mean arterial pressures during pregnancy, patients usually maintain normal blood pressures in the absence of underlying pathology [11 ▪ ]. Maternal systolic pressure <90–95 mmHg is associated with decreased uteroplacental circulation threatening fetal development [12].…”
Section: Physiologic Changes Of Pregnancymentioning
confidence: 99%
“…Physiologic respiratory alkalosis notwithstanding, maternal hypocapnia and hypercapnia must be avoided as both can interfere with placental oxygen delivery [52]. Since uteroplacental circulation lacks autoregulation, maternal hypotension can also lead to fetal acidosis [11 ▪ ,51].…”
Section: Anesthetic Recommendations: a Review Of Recent Literaturementioning
confidence: 99%
“…Preeclampsia is a complex pregnancy disorder for maternal and neonatal health and can be lifethreatening if not diagnosed early. It is marked by hypertension and potential organ damage, especially to the liver and kidneys, and is tied to diverse pathophysiological processes [1][2][3][4]. Oral and IV medications to lower blood pressure can be administered to the women to treat the disease until the baby is mature enough to be delivered.…”
Section: Introductionmentioning
confidence: 99%